Aboriginal children's health, playgroup participation and early learning outcomes in two remote Northern Territory communities. (August 2021) - Page, Jane; Murray, Lisa; Cock, Megan L; Eadie, Patricia; Nossar, Victor; Niklas, Frank; Scull, Janet; Sparling, Joseph
Objectives: This study aimed to explore the impact of early health risks on young Aboriginal children's attendance in playgroups and their early learning outcomes. Design: The study used a cross-sectional design to identify associations between children's early health characteristics, their attendance at a Families as First Teachers (FaFT) playgroup and their early learning outcomes. Setting: A total of 128 Aboriginal children from two remote Northern Territory (NT) communities attending FaFT playgroups participated in the study. Method: Health data were coded as risk factors and associated with children's attendance and learning outcome data. Results: Children in the cohort experienced relatively high rates of health risks: ear infections (otitis media, 57%), anaemia (37%), skin infections (28%), low birthweight (22%), low weight for age (19%) and a high proportion were born to teenage mothers (26%). However, these rates were lower than previously recorded rates for Aboriginal children in remote NT communities. Despite the presence of multiple health risks, low weight for age was the only risk factor found to be negatively associated with children's learning outcomes (language skills) and only two health risks (teenage motherhood and lower child haemoglobin levels) were negatively associated with children's attendance at playgroup. Most children (65%) experienced one or two health risks during the study and no significant associations were found between the number of health risks experienced and children's attendance or learning outcomes. Conclusion: The study highlights the importance of culturally responsive, evidence-based and integrated health and education programmes within remote Aboriginal Australian communities as a means to mitigate risks to poor learning and development outcomes.